PENGARUH E FAKTUR HOST TO HOST DAN E BUKPOT TERHADAP KEPATUHAN WAJIB PAJAK YANG DI MODERASI OLEH PENGAWASAN INTERNAL - Tambun, Sihar; Permana, Mochammad Fadzry Nikmatuloh (Universitas 17 Agustus 1945 Jakarta, 2019)
This study aims to prove the use of host-to-host and e-bupot e-invoices for tax obligations that are moderated by internal control. The factors considered in the current study are the use of invoices for hosts, hosts, tax involvement and internal controls. The analysis in this study is the independent variable e-invoice host to host, e-bupot and dependent variables ask for tax.This study uses primary data derived from the results of respondents in the research questionnaire. Researchers determined the number of samples based on Krejcie and Morgan's tables. Answering questions in this study were 32 tax employees at PT Astra International Tbk in the period after using e-invoice host to host and e-bupot. The selection of this study population used a purposive sampling method. The analytical method used in this study is multiple linear regression.The results of this study are that internal control cannot moderate the use of host-to-invoice e-invoices for taxpayer compliance because host-to-host e-factors, internal supervision cannot moderate the use of e-bukpot for taxpayer compliance, internal supervision does not significantly influence mandatory compliance tax, the use of e-bukpot has a positive and significant effect on taxpayer compliance. the use of host to host e-invoices has a significant effect on taxpayer compliance. Keywords: : E factur host to host, E Bukpot, tax compliance and internal control